Novel small-molecule inhibitors of arylamine N-acetyltransferases: drug discovery by high-throughput screening. - Westwood, I; Kawamura, A; Russell, A; Sandy, J; Davies, S; Sim, E (2011)
Arylamine N-acetyltransferases (NATs) are a family of enzymes found in eukaryotes and prokaryotes. While the precise endogenous function of NAT remains unknown for most organisms, recent evidence has shown that the expression of human NAT1 is up-regulated in estrogen receptor positive breast cancer. Additionally, NAT in mycobacteria is required for mycobacterial cell wall biosynthesis and survival of the organisms within macrophage. It is therefore important to develop small molecule inhibitors of NATs as molecular tools to study the function of NATs in various organisms. Such inhibitors may also prove useful in future drug design, for example in the development of anti tubercular agents. We describe a high-throughput screen of a proprietary library of 5016 drug-like compounds against three prokaryotic NAT enzymes and two eukaryotic NAT enzymes.